Consumption of Heated Palm Oil and its Effect on Kidney in Rats - Jaarin, Kamsiah; Yeen, Chan Pee; Masbah, Norliana (Pakistan Journal of Nutrition, 2016)
This research studied the effects of heated palm oil on serum creatinine and kidney histological changes in rats. Forty female Sprague-Dawley rats were divided into four groups (I to IV). Group I was fed with normal rats chaw (control). The groups II, III and IV were fed with rat chaw fortified with 15% weight/weight (w/w) fresh palm oil (FPO), heated five times palm oil (5HPO) and heated ten times palm oil (10HPO), respectively for a period of 16 weeks. Blood for serum creatinine was taken and determined at baseline and at the end of the study period using commercial kit and Cobas integra analyzer. The rats were sacrificed and the kidneys were weighed and examined histologically. The tissues were stained with haematoxylin and eosin. There was a significant reduction in the kidney’s weight in 5HPO and 10HPO group compared to fresh and control group. At the end of 16 weeks there was a significant increase in serum creatinine in all study groups compared to the respective baseline. However, there was no significant difference in serum creatinine in the palm oil fed groups compared with control. Histologically, localized congestion was noted in the tubular region of the kidney in the group fed with FPO, while diffuse congestion was observed in the glomerulus and tubular region of the group fed with 5HPO and 10HPO. There was also evidence of chronic inflammation with lymphocytes infiltration located in the tubular region of the groups fed with 5HPO and 10HPO. The inflammatory changes were more severe in 10HPO compared to 5HPO group. In conclusion; heated palm oil diet reduced kidney’s weight, causes tubular congestion and inflammation which were more severe in 10HPO compared to 5HPO. The histological changes were not accompanied by an increase in serum creatinine level.